2012
DOI: 10.3390/molecules17089469
|View full text |Cite
|
Sign up to set email alerts
|

Demethylzeylasteral Exhibits Strong Inhibition towards UDP-Glucuronosyltransferase (UGT) 1A6 and 2B7

Abstract: Inhibition of UDP-glucuronosyltransferase (UGT) isoforms can result in severe clinical results, including clinical drug-drug interactions (DDI) and metabolic disorders of endogenous substances. The present study aims to investigate the inhibition of demethylzeylasteral (an important active component isolated from Tripterygium wilfordii Hook F.) towards three important UGT isoforms UGT1A6, UGT1A9 and UGT2B7. The results showed that 100 μM of demethylzeylasteral exhibited strong inhibition towards UGT1A6 and UGT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…T-96 was reported to inhibit UGT1A6 (Ki = 0.6 μM) and UGT2B7 (Ki = 17.3 μM) 38 . It was originally used as an immunosuppressive agent, which significantly inhibited the activation of NF-κB 39 .…”
Section: Discussionmentioning
confidence: 99%
“…T-96 was reported to inhibit UGT1A6 (Ki = 0.6 μM) and UGT2B7 (Ki = 17.3 μM) 38 . It was originally used as an immunosuppressive agent, which significantly inhibited the activation of NF-κB 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies on TWHF toxicity have focused mainly on phase II metabolic enzymes. Zhao et al [21] demonstrated that demethylzeylasteral, an active ingredient of TWHF, strongly inhibits UGT1A6 and UGT2B7 in inhibitory studies on UGT1A6, UGT1A9, and UGT2B7. This observation indicates the need to monitor the potential clinical interactions between demethylzeylasteral-containing herbs and clinical drugs that mainly undergo UGT1A6-and UGT2B7-catalyzed metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…6,13 Moreover, AZT is primarily catalyzed by UGT2B7; 14 meanwhile, 4-MU, a nonspe-cic probe substrate for UGT isoforms, is oen used to investigate multiple UGT activities. 7,15 Therefore, estradiol, propofol, AZT, and 4-MU were used to evaluate the multiple glucuronidation activities in HLMs for this experiment.…”
Section: Discussionmentioning
confidence: 99%